المقاصد الشرعية في مصارف الزكاة وبعض تطبيقاتها المعاصرة (El-Wahat Journal for Research and Studies, 2020)
the purpose of this research is to detect the sharia objectives concerning zakat groups beneficiaries; in order to apply them in jurisprudential deductive relating to each group. it has adopted the analytical deductive method. the research has concluded that zakat tends to meet the needs of some types of society and to fulfil some of the ummah (muslim community)  duties. the research also concluded that several principles must be considered in zakat distribution; so that zakat will not be used for anything other than what it is set for. key words-zakat, islamic, purposes,  contemporary, application.